Dukungan Komunikasi Spiritual dalam Merawat Pasien - Nisa Ul Amina Siregar; Nurul Amanah Zebua; Putri Rizkia Simamora; Sandrio Dian Mikail (Young Journal of Social Sciences and Humanities, 2025)
This study aims to examine the importance of spiritual communication in healthcare, particularly in supporting the healing process of patients who are experiencing illness. Spiritual communication is seen as a non-medical approach that contributes to peace of mind, psychological strengthening, and increased patient motivation in dealing with illness. This study used a descriptive qualitative approach with data collection methods through observation, in-depth interviews, and documentation. Primary data sources were obtained from health workers and patients, while secondary data was collected from literature, journal articles, and other academic references. The results showed that spiritual communication, whether through prayer, strengthening beliefs, or spiritual support from family and medical personnel, plays a significant role in accelerating the patient's recovery process. Therefore, the integration of spiritual aspects in healthcare is essential to realize a holistic and humane approach to healing.